Comparative studies on Effect of Cations and Anions on controlled Release of Centchroman From Chitosan Microspheres - Loay Mohmmad Fadil AL-Emam (College of Education for Pure Sciences, 2010)
Abstract The Chitosan is a non-toxic, biocompatibale ploysacchride produced by deacetyltion of naturally occurring chitin. The mucoadhesitivity and biodegradability of chitosan have made chitosan as a choice material for developing various dosage forms for controlled delivery systems which are intended to deliver drugs at a controlled rate within a specified period of drug delivery. A comparative study on the degree of swelling and maximum loading and controlled drug released behavior were investigated for glutaraldehyde cross-linked chitosan microspheres in presence of different anions and cations and in the absence of these ions on burst and control release of centchroman. The addition of high charge density cations have reduced the amount of centchroman released in controlled manner, where as addition of anions has delayed the inception of controlled step of centchroman release and also decreased the amount centchroman released in this step.